Selective inhibition of nuclear factor‐κB by nuclear factor‐κB essential modulator‐binding domain peptide suppresses the metastasis of highly metastatic oral squamous cell carcinoma - Tanaka, Takuya (Cancer Sci, 2012)
Nuclear factor‐κB (NF‐κB) activation contributes to the development of metastasis, thus leading to a poor prognosis in many cancers, including OSCC. However, little in vivo experimental data are available about the effects of NF‐κB inhibition on OSCC metastasis. OSCC sublines were established from a GFP‐expressing parental cell line, GSAS, and designated GSAS/N3 and N5 according to the in vivo passage number after cervical lymph node metastasis by a serial orthotopic transplantation model. In vitro migration and invasion were assessed in these cells, and the NF‐κB activities and expression of NF‐κB‐regulated metastasis‐related molecules were also examined. In in vivo experiments, the metastasis and survival of tumor‐engrafted mice were monitored. Furthermore, the effects of a selective NF‐κB inhibitor, NEMO‐binding domain (NBD) peptide, on metastasis in GSAS/N5‐engrafted mice were assessed, and engrafted tongue tumors were immunohistochemically examined. Highly metastatic GSAS/N3 and N5 cells showed an enhanced NF‐κB activity, thus contributing to increased migration, invasion, and a poor prognosis compared with the parent cells. Furthermore, the expression levels of NF‐κB‐regulated metastasis‐related molecules, such as fibronectin, β1 integrin, MMP‐1, ‐2, ‐9, and ‐14, and VEGF‐C, were upregulated in the highly metastatic cells. The NBD peptide suppressed metastasis and tongue tumor growth in GSAS/N5‐inoculated mice, and was accompanied by the downregulation of the NF‐κB‐regulated metastasis‐related molecules in engrafted tongue tumors. Our results suggest that the selective inhibition of NF‐κB activation by NBD peptide may provide an effective approach for the treatment of highly metastatic OSCC. (Cancer Sci 2012; 103: 455–463)